Molecular and biological characterization of citrus bent leaf viroid from Malaysia - Iftikhar, Yasir; Khoo, Ying Wei; Murugan, Tanes; Roslin, Nor Athirah; Rabiatul Adawiyah; Kong, Lih Ling; Vadamalai, Ganesan (Springer, 2021)
Background: A 328-nucleotide variant of citrus bent leaf viroid (CBLVd) was characterized by citrus varieties in Malaysia. After the first report in Malaysia, the emerging CBLVd was detected in five citrus species, namely Citrofortunella microcarpa, Citrus aurantifolia, Citrus hystrix, Citrus maxima, and Citrus sinensis. Methods and results: CBLVd was detected in 23 out of 133 symptomatic samples through RT-PCR. Sequence analysis of the RT-PCR amplicons from this study showed 99–100% sequence identity to the reference CBLVd Jp isolate and CBLVd isolates reported in Malaysia. Inoculation of sap, obtained from a CBLVd positive sample, into 6-month old healthy C. microcarpa seedlings showed symptoms of slight leaf bending, reduced leaf size of matured leaves, and mild mosaic between 4 to 6 months after inoculation. Moreover, the observed symptoms of chlorosis, midvein necrosis, leaf rolling, and smalling of leaves in calamondin, C. microcarpa (Bunge) Wijnands, were not reported in earlier studies and opened a new avenue for the study of symptomology. The mechanical transmissibility of CBLVd in the inoculated seedlings was reconfirmed by RT-PCR assay and sequencing. Conclusions: Based on the results, the sequence similarity of CBLVd isolates from different areas of Malaysia showed no significant difference among each other and the reference isolate. The CBLVd is mechanically transmissible and could produce variable symptoms in different hosts.